Radio Frequency Modeling of Receive Coil Arrays for Magnetic Resonance Imaging - Stumpf, Christopher; Malzacher, Matthias; Schmidt, Lorenz-Peter (2018)
The numerical calculation of the signal-to-noise ratio (SNR) of magnetic resonance imaging (MRI) coil arrays is a powerful tool in the development of new coil arrays. The proposed method describes a complete model that allows the calculation of the absolute SNR values of arbitrary coil arrays, including receiver chain components. A new method for the SNR calculation of radio frequency receive coil arrays for MRI is presented, making use of their magnetic B1−" role="presentation">B−1 transmit pattern and the S-parameters of the network. The S-parameters and B1−" role="presentation">B−1 fields are extracted from an electromagnetic field solver and are post-processed using our developed model to provide absolute SNR values. The model includes a theory for describing the noise of all components in the receiver chain and the noise figure of a pre-amplifier by a simple passive two-port network. To validate the model, two- and four-element receive coil arrays are investigated. The SNR of the examined arrays is calculated and compared to measurement results using imaging of a saline water phantom in a 3 T" role="presentation">3 T scanner. The predicted values of the model are in good agreement with the measured values. The proposed method can be used to predict the absolute SNR for any receive coil array by calculating the transmit B1−" role="presentation">B−1 pattern and the S-parameters of the network. Knowledge of the components of the receiver chain including pre-amplifiers leads to satisfactory results compared to measured values, which proves the method to be a useful tool in the development process of MRI receive coil arrays.
Keywords: receive coil array; SNR modeling; MRI; pre-amplifier noise; noise coupling